Band-structure-based collisional model for electronic excitations in ion-surface collisions - Faraggi, Marisa Noemi (2005)
Energy loss per unit path in grazing collisions with metal surfaces is studied by using the collisional and dielectric formalisms. Within both theories we make use of the band-structure-based (BSB) model to represent the surface interaction. The BSB approach is based on a model potential and provides a precise description of the one-electron states and the surface-induced potential. The method is applied to evaluate the energy lost by 100 keV protons impinging on aluminum surfaces at glancing angles. We found that when the realistic BSB description of the surface is used, the energy loss obtained from the collisional formalism agrees with the dielectric one, which includes not only binary but also plasmon excitations. The distance-dependent stopping power derived from the BSB model is in good agreement with available experimental data. We have also investigated the influence of the surface band structure in collisions with the Al(100) surface. Surface-state contributions to the energy loss and electron emission probability are analyzed.